2023
DOI: 10.1039/d2nr05721b
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric upconversion luminescence nanoprobes from construction to sensing, imaging, and phototherapeutics

Abstract: In terms of the combined advantages from upconversion luminescence (UCL) properties and dual-signal ratiometric outputs toward specific targets, the ratiometric UCL nanoprobes exhibit significant applications. This review summarizes and discusses...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 201 publications
0
6
0
Order By: Relevance
“…In order to evaluate the capability of detecting temperature and performance of the developed optical thermometer, its thermal sensitivities were determined. The following equations can be used to figure out the relative and absolute temperature sensitivities (S r and S a ) 47,48 S T…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the capability of detecting temperature and performance of the developed optical thermometer, its thermal sensitivities were determined. The following equations can be used to figure out the relative and absolute temperature sensitivities (S r and S a ) 47,48 S T…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to evaluate the capability of detecting temperature and performance of the developed optical thermometer, its thermal sensitivities were determined. The following equations can be used to figure out the relative and absolute temperature sensitivities ( S r and S a ) , S a = FIR T S r = 100 % FIR × FIR T The S a and S r values for the NSYM phosphor as a function of temperature for different combinations of the Stark levels are shown in Figures S4a–f anda–f, respectively. In addition, Figure S5a,b shows the S a and S r values for two thermally coupled energy levels (TCLs) of Er 3+ (for the whole bands) in the temperature range of 298–330 K. For all determined thermometric parameters, including the FIR derived from different Stark components and from the whole TCLs bands, with increasing temperature, the S a increases while S r decreases.…”
Section: Resultsmentioning
confidence: 99%
“…[32] Depending on their size, structure, morphology, crystalline phase, and purity, UCNPs exhibit various upconversion photoluminescence efficiencies and emission wavelengths. [43,44] To date, numerous synthesis techniques have been employed to produce UCNPs, including thermal decomposition, coprecipitation, solvo-hydrothermal synthesis, solgel, microemulsion, electrospinning, mechanochemical preparation, and microwave synthesis. [45] Compared with QDs and traditional organic dyes, UCNPs have unique characteristics of minimizing the background interference due to autofluorescence of bio-samples and enhancing tissue penetration.…”
Section: Upconversion Nanophosphors (Ucnps)mentioning
confidence: 99%
“…In particular, the plasmon resonances could serve to achieve control over the luminescence properties of UCNPs by intentional amplification or quenching of the specific emission band [ 24 ], which could be beneficial for designing sensing platforms with specificity, low detection limits and linear response to the presence of the target bioanalyte. A recent literature survey has shown that several reviews related to the biosensing applications of UCNPs were published recently [ 7 , 14 , 25 , 26 ]. On the other hand, a focused overview of plasmon-modulated upconversion biosensing is still not available in the literature.…”
Section: Introductionmentioning
confidence: 99%